Motivasi Berprestasi Dan Disiplin Kerja Guru Sebagai Upaya Meningkatkan Efektivitas Organisasi (Studi pada Guru di MTsN Pare Kabupaten Kediri) - Supradono Sutopo; M. Naim Musyafik (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The purpose of this research is to know the Influence of Achievement Motivation Against Organizational Effectiveness, Influence of Teacher Work Discipline on Organization Effectiveness and Influence of Achievement Motivation and Teacher Work Disipli on Organizational Effectiveness Sample a total of 61 Permanent Teachers and Non-Permanent Teachers consisting of teachers at Islamic State Junior High School of Pare Kediri District took part in this research. This quantitative quantitative study uses regression analysis techniques. The results obtained show that: Motivation achievement significantly and affect the effectiveness of the organization, Teacher Work Discipline influence on organizational effectiveness and Achievement Motivation and Teacher Work Discipline together significantly affect the effectiveness of the organization Achievement Motivation and Teacher Work Discipline is one factor that can affect the effectiveness of the organization. The higher the discipline of Teacher work and achievement Motivation will make the organization effective.